Towards a standard archives and records management system for government corporation and financial institutions in Metro Manila - Golfo, Mary Grace P.; Gonzales, Grace Marie B.; Muñoz-Rey, Emma C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
It is the responsibility of any public servant to ensure that public records are protected, preserved and readily accessible and available when needed. Among government agencies, effective records management is a fundamental and core activity of public sector management (Wamukoya, 2000). Transparency and accountability in the dispatch of public service can be properly measured with an effective archives and records management program.
Aside from dispensing effective and efficient public service, GOCCs and GFIs are government instrumentalities which are also mandated to earn revenues for the government. In the performance of their mandated functions, these agencies are often subjected to risks of litigation from different stakeholders. Fast retrieval of accurate and complete records becomes very critical and important during performance audit and litigation.
This paper is a result of a survey on the current status of archives and records management (ARM) units of nine selected GOCCs and GFIs in Metro Manila. It gives an assessment of the position of the ARM units in their respective agencies, the personnel handling the units and existing ARM practices that these agencies have already adopted prior to the implementation of the The National Archives Act of the Philippines (R.A. 9470). It also identifies the level of compliance to required ARM tools as set by the Records Management and Archives Office (RMAO) and as set in ISO 15489. Findings show that although, 100 compliance to standards and best practices was not achieved by these agencies, efforts to put order in the handling of records and to protect and preserve records, particularly, archives are being undertaken. The lack of formal training or insufficient knowledge on the handling of archives, which was also identified in other earlier studies, also surfaced as a reason why basic requirements in archives administration are not implemented.
Based on the results of the study, the following major recommendations are presented in this paper: 1. Conduct a study that would require all agencies to come up with a separate records unit with the recommended level in the organization (similar to Procurement) based on the volume and importance of the records that the unit is expected to handle. 2. Formal training should be required to all personnel performing the functions of records management. A qualification standard (QS) which specifically requires formal training on records management and archives administration should be included in the position classification of the Civil Service Commission like upgrading the QS for training such that BLIS with Archives Track as major, BSPA (Public Administration), and/or AB History be specified as qualification standard. Unlike now that any four-year course is the only requirement in the QS for Archivists and Records Officers. 3. RMAO should come up with a standard for effective ARM specifically designed for GOCCs and GFIs. Proposed standard practices are also presented in this paper. 4. Conduct a study on the cost-benefit analysis of adopting a computerized records management system is also recommended.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Archives -- Management -- Philippines -- Manila Metropolitan Area; Records -- Philippines -- Management; Corporations, Government -- Philippines -- Manila Metropolitan. Area; Financial institutions -- Philippines -- Manila Metropolitan Area